(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
With the development of the energy industry, various types of problems began to arise related to the transmission, distribution, consumption, improvement of the quality of transmitted energy, as well as the problem of protecting networks from various types of damage. One of the problematic tasks of the power transmission system in networks with isolated neutral is protection against single phase short circuits to earth.